How Should a Progressive Parliament Advance Proportional Representation?. Issue 2 (24th May 2022) - White, Stuart
Abstract: Many supporters of democratic reform in the UK propose both a change in the electoral system to proportional representation (PR) and a shift to a formal (codified and entrenched) constitution. In principle, these two proposals are deeply complementary. There is, however, also a potential tension between them. Specifically, if a future UK government were to treat PR as a matter of ordinary legislation, this would conflict with the democratic constitutionalist principle that major constitutional changes require a more direct and/or robust test of public support, in addition to parliamentary approval—such as in a confirmatory referendum. The article discusses seven possible approaches by which a future progressive Parliament might advance PR. It assesses their strengths and weaknesses with an eye on this tension and other factors. It concludes that the emerging politics around this tension underscores the need for a formal constitution to prevent the UK's constitutional politics becoming subordinated to partisan conflict.